Upaya Preventif Pencegahan Tindak Pidana Korupsi Melalui Peningkatan Pemahaman Antikorupsi Terhadap Mahasiswa (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Eradicating corruption is one of the main concerns of the Indonesian government and nation. Corruption is considered an extraordinary crime so its eradication requires extraordinary efforts. Efforts to eradicate corruption consist of two main components, namely enforcement and prevention, but these efforts will never be optimally successful if implemented by the government itself without community participation. Therefore, the role of students in strengthening the anti-corruption movement is very important. Students' intelligence, youth and idealism are characteristics that make students play an important role in anti-corruption drives. In this research, the research method used is qualitative research with a literature review type of research (Library Research). One of the important goals for students to understand anti-corruption is that students can prevent themselves and others from committing corruption or committing acts of corruption, students have the courage to remind their family, relatives and friends around them not to commit corruption, and can also provide information to other people about corruption and eradicating corruption.